Patterns of Functional Disability in the Oldest Adults in China. Issue 9 (18th August 2016) - Fong, Joelle H.; Feng, Jun
Abstract : This study examined patterns of onset of activity of daily living (ADL) disability in a nationally representative sample of older adults in mainland China. Using longitudinal data from the Chinese Longitudinal Healthy Longevity Survey from 1998 to 2008 (N = 5, 570), nonparametric methods were used to evaluate median age at onset of various ADL disabilities and differences in the incidence of disabilities according to sex. The sampled older Chinese adults developed ADL disabilities, on average, between the ages of 89 and 94. Women were likely to experience later onset than men. The results also show that the oldest adults generally lose bathing ability, followed by toileting, transferring, dressing, eating, and finally, continence. This order—derived from estimated median age at onset—was also found to be highly prevalent in subsequently disabled respondents in the sample. The disability experience of older adults in China is somewhat similar to that of older adults in Western developed countries; elderly adults tend to lose ability in activities that require lower extremity strength earlier than those that require upper extremity strength. The relative importance of the various ADL items in the hierarchical ordering has implications for early intervention to reduce the risk of functional disability in older adults and those at risk of transitions of care.